Changes of cerebral oxygenation indices measured by near infrared time‐resolved spectroscopy during spinal anesthesia for cesarean section: Simultaneous measurement with cerebral blood flow. Issue 7 (4th May 2021) - Itosu, Yusuke; Kubo, Yasunori; Morikawa, Mamoru; Watari, Hidemichi; Morimoto, Yuji
Abstract: Aim: To measure the changes in cerebral oxygenation indices by near infrared time‐resolved spectroscopy and the cerebral blood flow simultaneously after spinal anesthesia for cesarean section. Methods: This prospective observational study was conducted for 25 pregnant women scheduled for elective cesarean section under spinal anesthesia. During a period of 15 min after spinal anesthesia, cerebral oxygenation (ScO2 ), and the total cerebral hemoglobin concentration (tHb) were measured using near infrared time‐resolved spectroscopy and mean cerebral blood flow velocity (Vm) was measured using transcranial Doppler ultrasonography. Next, in the women who had nausea during the observed period, we compared these values when nausea was detected with those when it was not. Results: Mean arterial pressure (MAP) decreased to around 60 mmHg (by 25% compared to the control) 6 min after spinal anesthesia. Compared to the control, ScO2 decreased by about 3% after 6 min and then gradually increased. The tHb, which reflects cerebral blood volume started to decrease just after spinal anesthesia and this continued until 12 min (the decrease was about 12%). Vm decreased by about 7%. In the 14 women who had nausea, MAP, Vm, and ScO2 values when nausea was detected were significantly lower than when it was not. Conclusion: The changes in cerebral hemodynamics may be small after spinal anesthesia in ordinary cesarean section compared to the reduction of systemic arterial blood pressure. There might be greater decreases in cerebral blood flow and oxygenation when nausea occurred in the pregnant women who experienced it after spinal anesthesia.